Quality of life of elderly people enrolled in a health care program and associations with the characteristics of the patient, the disease, the therapy, and social support - Giovana Caldas Pereira; Beatriz Pavan Campos; Marcela Reis Pedrasini Shimazaki; Claudia D`Arco; Ivonete Sanches Giacometti Kowalski; Maria Inês Nunes; Carla Maria Maluf Ferrari (O Mundo da Saúde, 2022)
The increase in life expectancy among individuals over 65 years of age has changed the age pyramid of the Brazilian population. Quality of life (QoL) is an important parameter to assess health status. The aim of the study was to describe the QoL of elderly people enrolled in an elderly care program, showing associations with the characteristics of the patient, disease, therapy, and social support, contributing to improve care for the elderly who receive this service. This was a descriptive, quantitative, cross-sectional, correlational study with 85 individuals aged 60 years or more, who were literate, independent in activities of daily living, without diagnosed cognitive/psychological impairment, and who had been going to the Nossa Senhora do Rosário Social Center for at least one month. To collect the independent variables, an instrument developed by the authors was used; in addition to the Morisk-Green test and Medication Regimen Complexity Index (MRCI). QoL was assessed by WHOQOL-brief. 89.4% were women; 38.8% were 60 to 70 years old; 77.6% had up to 3 comorbidities, the most frequent was hypertension (77.65%); 49.41% used polypharmacy, the MRCI ranged from 2.5 to 48.0 points for one to twelve medications/day; 57.65% acquired their medication through the SUS; 64.80% had medium/low adherence; 43.53% declared having a good perception of health. As for the WHOQOL-brief domains, the highest mean was obtained in the social domain (75.5), followed by the psychological (68.3), physical (67.1), and environmental (64.8) domains. The results of this study highlighted that the female gender, presence of diseases, therapeutic complexity, and perception of poor health are associated with lower quality of life indices in this population.